Infection in Immunocompromised Hosts: Imaging. Issue 5 (September 2018) - Tanaka, Nobuyuki; Kunihiro, Yoshie; Yanagawa, Noriyo
Abstract : Immunocompromised patients are encountered with increasing frequency in clinical practice. In addition to the acquired immunodeficiency syndrome (AIDS), therapy for malignant disease, and immune suppression for solid organ transplants, patients are now rendered immunosuppressed by advances in treatment for a wide variety of autoimmune diseases. The number of possible infecting organisms can be bewildering. Recognition of the type of immune defect and the duration and depth of immunosuppression (particularly in hematopoietic and solid organ transplants) can help generate a differential diagnosis. Radiologic imaging plays an important role in the detection and diagnosis of chest complications occurring in immunocompromised patients; however, chest radiography alone seldom provides adequate sensitivity and specificity. High-resolution computed tomography (CT) can provide better sensitivity and specificity, but even CT findings may be nonspecific findings unless considered in conjunction with the clinical context. Combination of CT pattern, clinical setting, and immunologic status provides the best chance for an accurate diagnosis. In this article, CT findings have been divided into 4 patterns: focal consolidation, nodules/masses, small/micronodules, and diffuse ground-glass attenuation/consolidation. Differential diagnoses are suggested for each pattern, adjusted for both AIDS and non-AIDS immunosuppressed patients.